Understanding the Hermeneutic Debate as a New Method of Understanding Hadis - Sifa, Alex Nanang Agus; Adha, Ahmad Faizal (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2019)
The discourse on hermeneutic in the study of interpreting the sources of Islamic law is still widely discussed by Muslim intellectuals until now. Apart from being used as a method of interpreting the Qur'an, hermeneutic is also used by some Muslim academics to interpret hadis. But in its application, there are still debates between them. Some of them accept the presence of hermeneutic as one of the relevant methods used to understand the hadis, but others reject it. The reason of the receiving party is based on the need for hermeneutic in understanding the hadis, especially to answer contemporary problems that have not yet been resolved in understanding the hadis before. The reason for the refusing party is because this hermeneutic method was born from the West and is used to understand the Bible that has different characteristics from the hadis. This paper tries to examine the hermeneutic study of hadith proportionally by looking at the reasons behind the acceptance and rejection of the hermeneutic method in the interpretation of the hadis. In addition, this paper also elaborates on the issue of hermeneutic application related to the science of balaghah which is the original product of previous Muslim scholars.